2015
DOI: 10.1097/bpb.0000000000000146
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and epidemiology of pediatric musculoskeletal injuries in Kashmir valley, a retrospective single-center study of 1467 patients

Abstract: This work aimed to study the pattern and epidemiology of pediatric musculoskeletal trauma and consequent morbidity in Kashmir Valley and compare the results with other studies and to formulate preventive measures and devise management strategies. This was a retrospective study of 1467 pediatric orthopedic trauma patients who presented to our hospital over a 3-year period between September 2005 and August 2008. Information was recorded in a prescribed proforma including the following: age, sex, mode of trauma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 35 publications
7
25
1
2
Order By: Relevance
“…Hussain et al [19] also found that the common fracture sites were around the elbow in the preschool age group and the forearm in school children. In our study, a similar trend, wherein the most common fracture site was upper limbs, was noted in both non-ADHDs and ADHDs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Hussain et al [19] also found that the common fracture sites were around the elbow in the preschool age group and the forearm in school children. In our study, a similar trend, wherein the most common fracture site was upper limbs, was noted in both non-ADHDs and ADHDs.…”
Section: Discussionmentioning
confidence: 95%
“…An epidemiologic study in Malmö indicated that the risk of sustaining a fracture in children is 42% in boys and 27% in girls from birth to age 16 years [12]. Hussain's research showed that fractures in males outnumber those of females in every age group ranging from 0 to 16 years (the overall male-to-female ratio was 2.12 : 1) [19]. Other studies also showed that the risk of fracture in boys is higher than that in girls [2,20 -22].…”
Section: Discussionmentioning
confidence: 97%
“…No studija Hassaina i sur. u analizi 1467-ero djece regije Kashmir (Indija) bolnički liječene zbog prijeloma, nalazi kako su najčešća mjesta nastanka prijeloma kuća 41,1% i igrališta 30,7%, prometnice 14,9%, škola 12,5% (29).…”
Section: Raspravaunclassified
“…No, prema studiji Hassaina i sur., analizom 1467ero djece iz regije Kašmir (Indija), bolnički lije čene zbog prijeloma, utvrđeno je da je najčešće mjesto nastanka prijeloma kuća -41,1%; slijede igrališta -30,7%, prometnice -14,9% i škola -12,5%. 29 U pro metu nastaje iznimno malo prijeloma kostiju podlak tice. Jesu li preventivne mjere koje provodi MUP RH razlog tomu?…”
Section: Raspravaunclassified